Synthesis and Crystal Structure of Dialkoxo-Bridged Dinuclear Cu(II) Complex with 5-Methoxy-6’-hydroxy-2,2’-[ethylenedioxybis(nitrilomethylidyne)]diphenol - Zhang, Xin-Ying; Zhang, Li-Sha; Liu, Peng-Fei; Yang, Cheng-Juan; Wang, Zheng-Kun; Meng, Jiao-Long (Asian Journal of Chemistry, 2013)
An unexpected dinuclear copper(II) complex, [Cu2(L2)2] (H2L2 = 4-methoxysalicylaldehyde-O-(2-hydroxyethyl)oxime), has been synthesized through the complexation of Cu(OAc)2·H2O with an asymmetrical salamo-type compound 5-methoxy-6'-hydroxy-2,2'-[ethylenedioxybis(nitrilomethylidyne)]diphenol (H3L1). The catalysis of Cu(II) ions results in the unexpected cleavage of one of the N-O bonds in the ligand H3L1, giving a novel dialkoxo-bridged dinuclear Cu(II) complex possessing a Cu-O-Cu-O four membered ring core instead of the usually desired salamo-type ligand Cu-N2O2 mononuclear complex.